Evidence for Distinct Substrate Specificities of Importin α Family Members in Nuclear Protein Import - Köhler, Matthias (American Society for Microbiology, 1999)
Importin α plays a pivotal role in the classical nuclear protein import pathway. Importin α shuttles between nucleus and cytoplasm, binds nuclear localization signal-bearing proteins, and functions as an adapter to access the importin β-dependent import pathway. In contrast to what is found for importin β, several isoforms of importin α, which can be grouped into three subfamilies, exist in higher eucaryotes. We describe here a novel member of the human family, importin α7. To analyze specific functions of the distinct importin α proteins, we recombinantly expressed and purified five human importin α’s along with importin α from Xenopus and Saccharomyces cerevisiae. Binding affinity studies showed that all importin α proteins from humans or Xenopus bind their import receptor (importin β) and their export receptor (CAS) with only marginal differences. Using an in vitro import assay based on permeabilized HeLa cells, we compared the import substrate specificities of the various importin α proteins. When the substrates were tested singly, only the import of RCC1 showed a strong preference for one family member, importin α3, whereas most of the other substrates were imported by all importin α proteins with similar efficiencies. However, strikingly different substrate preferences of the various importin α proteins were revealed when two substrates were offered simultaneously.